Evaluation of three sample preparation methods for the identification of clinical strains by using two MALDI‐TOF MS systems. (9th January 2021) - Wang, Jinghua; Wang, Hualiang; Cai, Keya; Yu, Peijuan; Liu, Yajuan; Zhao, Gaoling; Chen, Rong; Xu, Rong; Yu, Maowen
Abstract: Matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) has revolutionized the microbial identification, especially in the clinical microbiology laboratories. However, although numerous studies on the identification of microorganisms by MALDI‐TOF MS have been reported previously, few studies focused on the effect of pretreatment on identification. Due to the sensitivity of MALDI‐TOF MS, different preparation methods will lead to changes in microbial protein fingerprints. In this study, for evaluating a more appropriate preparation method for the clinical microbiology identification, we analyzed the performance of three sample preparation methods on two different MALDI‐TOF MS systems. A total of 321 clinical isolates, 127 species, were employed in the comparative study of three different sample preparation methods including the direct colony transfer method (DCTM), the on‐target extraction method (OTEM), and the in‐tube extraction method (ITEM) compatible with MALDI‐TOF MS. All isolates were tested on the Microflex LT and Autof ms1000 devices. The spectra were analyzed using the Bruker biotyper and the Autof ms1000 systems. The results were confirmed by 16/18S rRNA sequencing. Results reveal that the accuracies of isolates identification by Bruker biotyper successfully identified 83.8%, 96.0%, and 95.3% after performing the DCTM, OTEM, and ITEM, respectively, while the Autof ms1000 identified 97.5%, 100%, and 99.7%. These data suggested that the identification rates are comparable among the three preparation methods using the Autof ms1000 and Bruker microflex LT systems but the OTEM is more suitable and necessary for clinical application, owing to its key advantages of simplicity and accuracy.